Modeling female identity In Two Neighbors, by Wilhelm Rotermund - Grützmann, Imgart (2019)
Dr. Wilhelm Rotermund, evangelical pastor, journalist and bookseller in São Leopoldo/RS, was also a writer, standing out in the short story genre. His literary productions in German were published in the Kalender für die Deutschen in Brasilien [Almanac for the Germans in Brazil], between 1881 an 1898, a periodical edited annually, focused on the information and formation o readers. In this article, the objective is to analyze two female characters from the tale Die beiden Nachbarn. Bilder aus der Kolonie [Two neighbors. Scenes of the colony], by Rotermund, who are mobilized in the mentioned narrative with the purpose of affirming and spreading a German feminine evangelical rural identity. This analysis is based on the considerations of Tomaz Tadeu da Siva on identity and of Philippe Poutignat and Jocelyne Sreiff-Fenart regarding ethnic identity.